Potensi Minuman Fermentasi Sinbiotik Berbasis Buah Lokal Indonesia Dan Bakteri Asam Laktat Indigenous: Tinjauan Sistematis Atas Viabilitas Probiotik, Karakteristik Fungsional, Dan Arah Pengembangan - Cornelius Hari Wibowo; Antonia Nani Cahyanti; Iswoyo Iswoyo; Maria Sudjatinah (Jurnal Teknologi Pangan dan Hasil Pertanian, 2026)
Indonesia possesses a diverse array of local fruits and indigenous lactic acid bacteria (LAB) derived from traditional fermented foods, which hold potential for development into synbiotic fermented beverages. Nevertheless, research findings on the integration of local fruits and indigenous LAB remain dispersed across various individual publications and have not been systematically synthesized. Objective: This study seeks to map the combinations of local Indonesian fruits and indigenous LAB that have been investigated, synthesize the characteristics of probiotic viability and the physicochemical-functional properties of the resulting products, and identify challenges and directions for future research. Methods: A systematic literature review was conducted in accordance with the PRISMA guidelines, utilizing databases such as Scopus, Google Scholar, Scimago Journal Rank, and Garuda/Sinta, with a focus on primary literature from 2020 to 2026 and references to pertinent foundational concepts. Results: At least 15 types of local Indonesian fruits, including Manalagi apple, mango, soursop, snake fruit, tamarillo, guava, eggplant, and pineapple, were combined with native LAB and selected starter cultures to produce synbiotic beverages with viability ranging from 10^8 to 10^10 CFU/mL and a final pH of 3.8 to 4.9, which were generally sensorially acceptable. This study also identified research gaps in storage stability, probiotic encapsulation, and human clinical trials. Conclusion: Local Indonesian fruits and native LAB exhibit significant potential as raw materials for functional synbiotic beverages; however, further translational research is necessary to facilitate product downstreaming.